2018
DOI: 10.1016/j.compstruct.2018.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Meta-tensegrity: Design of a tensegrity prism with metal rubber

Abstract: A tensegrity structure involves the presence of elements withstanding pure compression, and others under pure tension only. Metal rubber is introduced into a tensegrity prism strut to create a mechanical metamaterial with energy absorption and tuneable dynamic properties. In this work we describe the design and development of the meta-tensegrity structure with particular emphasis on the evaluation of parameters such as the structural size, the metal rubber stiffness, the initial internal force and the external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…According to the experimental results of Wang et al [31], the effective Poisson's ratio ν yx was approximately zero. Zhang et al [19] reported that the tangent Poisson's ratio of MR was approximately 0.01 at small deformations and could reach 0.1 at large deformations.…”
Section: Principle Of the Constitutive Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the experimental results of Wang et al [31], the effective Poisson's ratio ν yx was approximately zero. Zhang et al [19] reported that the tangent Poisson's ratio of MR was approximately 0.01 at small deformations and could reach 0.1 at large deformations.…”
Section: Principle Of the Constitutive Modelmentioning
confidence: 92%
“…Zhu et al [30] analyzed three types of contact status of micro helix springs under the assumption that the spatial distribution of the microelements inside the MR is even and periodic. On that basis, they built a mathematical model to describe the behavior of the MR. Ma et al [31] introduced MR into the tensegrity structure to improve energy absorption and reduce the stiffness, and they presented a mathematical model of tensegrity based on the nonlinearity mechanics of MR. The pyramid model was used to describe the principle of energy dissipation of MR. Before calculating the horizontal and vertical friction pair, it is necessary to experimentally identify the coefficient of the MR and the angle of the pyramid contact pair [32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dynamic performance of EWMs under large deformations needs be investigated for their potential use in the novel biologically-inspired bridge pier. Entangled metal wires have multifunctional applications, and have been also recently proposed as energy dissipating units in tensegrity prisms systems ( [39], [40]). It is worth noticing that tensegrity prism does possess mechanical behaviours similar to the human spine [41], and also offers interesting static and dynamics performance in a lightweight design in civil constructions [42], [43], [44].…”
Section: Entangled Wire Materialsmentioning
confidence: 99%
“…Metal wire-based pseudo-rubber, which is also called metal rubber (MR) (Ma et al, 2018;Zhang et al, 2013), and entangled metallic wire materials (Gadot et al, 2015) have been fabricated and investigated by several research groups over the past decades. These types of porous materials are usually fabricated using thin stainless-steel wires or SMA wires (0.1-0.5 mm in diameter) through wrapping, weaving, rolling, and stamping processes.…”
Section: Smaprmentioning
confidence: 99%